Synchronous Cervical Minimal Deviation Adenocarcinoma, Gastric Type Adenocarcinoma and Lobular Endocervical Glandular Hyperplasia Along with STIL in Peutz-Jeghers Syndrome: Eliciting Oncogenesis Pathways - Azfar NEYAZ; Nuzhat HUSAIN; Manish DEODHAR; Rohini KHURANA; Saumya SHUKLA; Aditi ARORA (Federation of Turkish Pathology Societies, 2019)
We describe an unusual case of a Peutz-Jeghers syndrome associated with a composite synchronous cervical neoplasia comprising precursor "lobular endocervical glandular hyperplasia (LEGH)", "minimal deviation adenocarcinoma (MDA)" and "gastric-type adenocarcinoma (GTA)" along with a serous tubal intraepithelial lesion (STIL) in the right fallopian tube. A 24-year-old woman presented with a white mucoid discharge and bleeding per vaginum for one year. Histopathological evaluation showed MDA & GTA in FIGO grade III with pelvic lymph node metastasis despite a deceptively bland tumour morphology and low Ki-67 index, indicating an aggressive tumour course and poor prognosis. Diagnostic marker profile in the cervix showed gastric type mucin and positive expression of CK-7, CK-20 (patchy), CEA, and negative CDX-2, p16, ER and PR. Further an attempt at eliciting the oncogenesis pathway in view of the p16 and HPV negative nature of the gastric type cervical adenocarcinoma showed negativity for p53 but activation of cyclin D1. Growth factors including Her2 and EGFR were negative while VEGFR was over-expressed. She was treated by radical hysterectomy and pelvic radiation. She was free from recurrence at the 12-month follow-up. This is a first-time report of a STIL in the fallopian tube which was validated by a unilateral mutant type p53 expression and increased Ki67 index, associated with synchronous gastric type adenocarcinoma of the cervix in all stages of evolution.